Peran Inovasi Dalam Membangun Keunggulan Bersaing Sektor UMKM Bidang Kuliner Pascadisrupsi Akibat Pandemi Covid 19 Di Kota Bandung - Maya Setiawardani (Jurnal Riset Bisnis dan Investasi, 2022)
The purpose of this study is to identify the innovations that have been built by culinary SMEs and the level of competitive advantage after the disruption due to the Covid-19 pandemic, and to reveal how big the role of innovation is in building competitive advantage. The research method used is a quantitative method, the sampling technique uses non-probability sampling with a purposive sampling approach of 100 respondents. Data was collected through a questionnaire using a Likert scale. The data were processed by SPSS, and used descriptive analysis, correlation analysis, multiple regression analysis, partial determination coefficient analysis and hypothesis testing. The results of this study indicate that the level of innovation built by culinary SMEs is included in the sufficient category and the level of competitive advantage is high, and innovation has a significant role in building a competitive advantage of 46.2%.